Mudanças sobre a Cultura Organizacional no processo de transição de Banco Estadual para Banco Privado - Ribeiro, Kalina Lígena Lira de Miranda (2008)
The present work has as objective to analize the main changes that occur in the organizational culture of a State Bank that passed for a privatization process, and today are part of a private banking group, with the perspective of the organizational culture based on the Model of Architecture of the Organizational Culture - LANDMARK. The model Landmark brings the culture as a social construction of the collective body, that reflects the auto-image of an organization. The research is characterized as a study of case of descriptive exploratory approach and purely qualitative boarding. The citizens of the research had been the collaborators who had worked in the State Bank and today are placed in the agencies of the Private bank. For collection of the data it was used of half-structuralized interviews. The technique used for interpretation of the data was the analysis of content of Bardin (1977). The results of the carried through interviews had shown that the organizational culture presented well significant changes in all the studied dimensions. In the transition process, the collaborators had lived deeply new practical administrative who had forced a change of behavior in the day the organizational day, resulting in a cultural renewal. One of the main aspects desencadeadores of all mannering process occurred in the dimension necessities with the perspective change that previously the collaborators had its functional stability and currently the main changes in the too much dimensions fight for its permanence in the organization stimulating. In the dimension values, the collaborators had had that to disconfirmed or to substitute the existing values in the State Bank and to assume the new values of the Private bank. As for the dimension knowledge, the collaborators are stimulated by the organization to have a professional formation and search as many common knowledge s how much specific therefore they consider that its current function requires a bigger gamma of knowledge. Finally in the dimension abilities, it was evidenced that when stimulating the professional formation of its collaborators, the company is increasing the intellectual level of each one, with this improves each time its abilities techniques.